Non‐invasive prenatal diagnosis – erythrocyte and platelet antigens. (April 2015) - van der Schoot, C. E.; Thurik, F. F.; Scheffer, P. G.; Veldhuisen, B.; de Haas, M.
<x xml:space="preserve">Abstract</x> Non‐invasive fetal blood group typing.